Instituições e práticas escolares como representações de modernidade em Pelotas (1910-1930): imagens e imprensa - Oliveira, Maria Augusta Martiarena de (2012)
This research is dedicated to analyze the school culture (institutions and school practices) which was used as elements of social distinction of pelotense elite, to comprove the modernity of the practices and institutions related to that group. For the achievement of this research we used written and iconographic sources, extracted from the city of Pelotas press and official documents. This research is developed about the 1910 to 1930 decades, a period characterized as a transitional context.. We realize that, at that juncture, the Pelotense elite used the educational institutions and their school practices as representations of educational and urban modernity. For realizing this research we found in the New Cultural History, especially Le Goff and Burke, a basis. For working with images we chose an approximation with authors who have worked with photos, such as Kossoy, Freund, Bauret, Fabris and Leite. The references used to assist in working with the press was, mainly, Luca and Bastos. On the history of educational institutions, school culture and school architecture, met basement, especially in Frago, Escolano, Julia, Werle, Magalhães and Bencostta. For the contextualization of the period studied, it was used, notably, Nagle, Carvalho, Faria Filho e Souza, at the national level, and Corsetti, Pesavento and Tambara in regional context. With respect to the concept of elite and distinction, we chose the approach of Bourdieu. The analysis of the sources coupled with theoretical allowed the perception of how certain practices, especially Scouting, exhibitions of handicrafts and civic events were used to update the elite pelotense s state in relation to modernity. Moreover, some institutions were directly linked to the ideology of the elite, such as the School of Agronomy and Veterinary. In this study, one notices a clear distinction between education and grassroots education elites. It is noteworthy, though, the role of philanthropy in visbilidade of that group.